Proposed Software Testing Using Intelligent techniques (Intelligent Water Drop (IWD) and Ant Colony Optimization Algorithm (ACO)) - Alzubaidy, Laheeb M; Alhafid, Baraa S (International journal of computer science issues, 2013)
This paper proposed software testing system by using artificial intelligent techniques. And that was conducted through Suggestion Intelligent Water Drop Algorithm (IWD) with white box testing for generated basis bath testing and using Ant Colony Optimization Algorithm (ACO) for test data generation. Correctly generated Test data helps in reducing the effort while testing the software. Automatic generation of test data is required to enables the corporation which develops the program to save time and costs as well as ensuring the test process quality, which is estimated by 50% of the product cost.